Procalcitonin and Presepsin as Prognostic Markers After Out-of-Hospital Cardiac Arrest. Issue 4 (October 2018) - Pekkarinen, Pirkka T.; Ristagno, Giuseppe; Wilkman, Erika; Masson, Serge; Latini, Roberto; Laurikkala, Johanna; Bendel, Stepani; Ala-Kokko, Tero; Varpula, Tero; Vaahersalo, Jukka; Karlsson, Sari; Tiainen, Marjaana; et al.
ABSTRACT: Background: Patients resuscitated from cardiac arrest commonly develop an inflammatory response called post-cardiac arrest syndrome that clinically resembles septic shock. Procalcitonin and presepsin are associated with inflammation. We hypothesized that these biomarkers reflect the severity of post-cardiac arrest syndrome and predict short-term hemodynamical instability and long-term neurological outcome after cardiac arrest. Methods: As a subcohort analysis of a prospective, observational, multicenter study "FINNRESUSCI, " we obtained plasma from 277 intensive care unit (ICU) patients treated following out-of-hospital cardiac arrest (OHCA). Procalcitonin and presepsin levels were measured 0 to 6 h from ICU admission and 24, 48, and 96 h thereafter. We defined poor outcome as a 12-month Cerebral Performance Category of 3 to 5. We tested statistical associations between biomarkers and hemodynamical parameters and outcome with regression models. Results: Plasma procalcitonin had best predictive value for 12-month poor outcome at 96 h (AUC 0.76; 95% CI 0.68–0.83) and presepsin at ICU admission (AUC 0.72; 95% CI 0.65–0.78). Elevated procalcitonin concentration at ICU admission predicted unstable hemodynamics in the following 48 h in a linear regression model. In a multivariate logistic regression model with clinical variables, only procalcitonin at 96 h had independent prognostic value for poor 12-month neurological outcome. Conclusions: Elevated procalcitonin is associated with hemodynamical instability and worsened long-term outcome in OHCA patients. The association is not strong enough for it to be used as a single predictor. Presepsin did not provide clinically relevant information for risk stratification after OHCA. Abstract : Supplemental Digital Content is available in the text